Why Alliances Fail: Islamist and Leftist Coalitions in North Africa. Matt Buehler. New York : Syracuse University Press, 2018. xiv + 288 pp. $75.00 cloth, $33.00 paper. - Driessen, Michael Daniel (Politics and religion, 2020)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS1755048320000164/resource/name/firstPage-S1755048320000164a.jpg